2017
DOI: 10.1161/atvbaha.117.309574
|View full text |Cite
|
Sign up to set email alerts
|

ABCA8 Regulates Cholesterol Efflux and High-Density Lipoprotein Cholesterol Levels

Abstract: ABCA8 facilitates cholesterol efflux and modulates HDLc levels in humans and mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 38 publications
5
47
1
Order By: Relevance
“…In contrast, as an example of HSAGs, ATP Binding Cassette Subfamily A Member 8 ( ABCA8 ) showed strong upregulation with age (FDR = 8.15 × 10 −3 ) in the “healthy” cohort (Figure e and Figure d), while no association was observed in the “unhealthy” cohort (FDR = 0.23). HDLc levels were found decreased by 29% ( p = .01) in ABCA8 deficiency mice on a high‐cholesterol diet compared with wild‐type mice (Trigueros‐Motos et al, ). ABC transporters protect cells against unrelated (toxic) substances by pumping them across cell membranes (Tang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, as an example of HSAGs, ATP Binding Cassette Subfamily A Member 8 ( ABCA8 ) showed strong upregulation with age (FDR = 8.15 × 10 −3 ) in the “healthy” cohort (Figure e and Figure d), while no association was observed in the “unhealthy” cohort (FDR = 0.23). HDLc levels were found decreased by 29% ( p = .01) in ABCA8 deficiency mice on a high‐cholesterol diet compared with wild‐type mice (Trigueros‐Motos et al, ). ABC transporters protect cells against unrelated (toxic) substances by pumping them across cell membranes (Tang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…After data filtering, a novel nonsense mutation (NM_007168: c.3460C>T; p.R1154X) of ABCA8 was identified and validated by Sanger sequencing in the proband (Figure 1E). Previous studies have revealed that deleterious heterozygous ABCA8 mutations may disrupt cholesterol efflux and reduce HDL-c levels in humans and mice (Trigueros-Motos et al, 2017;Sasaki et al, 2018). No other meaningful mutations related to lipid metabolism has been identified.…”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…However, the underlying cause of reduced HDL-c values was still not clear. Several genes including ATP binding cassette subfamily A member 1 (ABCA1) and ATP binding cassette subfamily A member 8 (ABCA8) have been identified in patients with reduced HDL-c (Trigueros-Motos et al, 2017;Maranghi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additional ABCA family proteins are involved in cholesterol efflux. ABCA8 facilitates cholesterol efflux to apoA-I and modulates HDL-cholesterol levels ( 192 ). In humans, mutations in this gene are associated with low HDL-cholesterol levels ( 192 ).…”
Section: Sterol Export To Extracellular Milieumentioning
confidence: 99%
“…ABCA8 facilitates cholesterol efflux to apoA-I and modulates HDL-cholesterol levels ( 192 ). In humans, mutations in this gene are associated with low HDL-cholesterol levels ( 192 ). In addition, ABCA12 also regulates cholesterol efflux ( 193 ).…”
Section: Sterol Export To Extracellular Milieumentioning
confidence: 99%